Teologi Ekologi: Suatu Isu Etika Menuju Eskatologi Kristen - Jefri Hina Remikatu (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2020)
Abstract. The issues of Christian ethics and eschatology are two important parts that being discussed in this paper regarding the ecological crisis that is happening recently. These two issues invite the the church to rethink the missiological and soteriogical concept so that it can influence the activity of the church in carrying out the mission of God. The church become the agen of God in voicing out the renewal of the broken relationship become harmony. Therefore, the mission mandate that carried out by the church should be understood as participation of the church in the dynamic fellowship harmony with God and with all creations. The church as a community of the believers that has a dynamic fellowship with God will actively participate in God’s mission. As the agen of God, the church must carry out her role in manifesting the divine mission through the proclamation of the salvation from God, trying to create and bring peace and harmony through the ethical behavior and bring the message of hope that everything must be turned to the glory of God as the soteriological hope for all creations in union with Him. So, this paper challenges the church to reevaluate the Great Commission that contained in the Old Testament especially in the book of Genesis and New Testamen in the book of Matthew.Abstrak. Isu etika dan eskatologi Kristen merupakan dua bagian penting yang dipercakapkan makalah ini terkait krisis ekologi yang sedang terjadi. Kedua isu tersebut mengajak gereja untuk memikirkan ulang konsep misi dan konsep keselamatan sehingga dapat mempengaruhi aktivitas gereja dalam menjalankan misi Allah. Gereja menjadi agen Allah dalam menyuarakan pembaharuan relasi yang rusak menjadi harmonis. Karena itu mandat misi yang dijalankan oleh gereja dipahami sebagai partisipasi gereja dalam persekutuan harmonis yang dinamis dengan Allah. Gereja sebagai komunitas orang-orang percaya yang memiliki hubungan yang dinamis dengan Allah akan secara aktif berpartisip dalam misi Allah. Sebagai Agen Allah, gereja harus menjalankan perannya dalam mengejawantahkan misi ilahi melalui proklamasi keselamatan dari Allah, berusaha membawa damai maupun keharmonisan melalui prilaku etis, serta menyampaikan berita pengharapan bahwa segala sesuatu harus dikembalikan kepada kemuliaan Allah sebagai pengharapan soteriologis dalam penyatuan dengan Dia. Makalah ini memberikan tantangan kepada gereja untuk mengevaluasi Amanat Agung yang terdapat dalam Perjanjian Lama terkhusus dalam kitab Kejadian dan Perjanjian Baru dalam Injil Matius.